Respuesta :
[tex]y'=(t+y)^2-1[/tex]
Substitute [tex]u=t+y[/tex], so that [tex]u'=y'[/tex], and
[tex]u'=u^2-1[/tex]
which is separable as
[tex]\dfrac{u'}{u^2-1}=1[/tex]
Integrate both sides with respect to [tex]t[/tex]. For the integral on the left, first split into partial fractions:
[tex]\dfrac{u'}2\left(\frac1{u-1}-\frac1{u+1}\right)=1[/tex]
[tex]\displaystyle\int\frac{u'}2\left(\frac1{u-1}-\frac1{u+1}\right)\,\mathrm dt=\int\mathrm dt[/tex]
[tex]\dfrac12(\ln|u-1|-\ln|u+1|)=t+C[/tex]
Solve for [tex]u[/tex]:
[tex]\dfrac12\ln\left|\dfrac{u-1}{u+1}\right|=t+C[/tex]
[tex]\ln\left|1-\dfrac2{u+1}\right|=2t+C[/tex]
[tex]1-\dfrac2{u+1}=e^{2t+C}=Ce^{2t}[/tex]
[tex]\dfrac2{u+1}=1-Ce^{2t}[/tex]
[tex]\dfrac{u+1}2=\dfrac1{1-Ce^{2t}}[/tex]
[tex]u=\dfrac2{1-Ce^{2t}}-1[/tex]
Replace [tex]u[/tex] and solve for [tex]y[/tex]:
[tex]t+y=\dfrac2{1-Ce^{2t}}-1[/tex]
[tex]y=\dfrac2{1-Ce^{2t}}-1-t[/tex]
Now use the given initial condition to solve for [tex]C[/tex]:
[tex]y(3)=4\implies4=\dfrac2{1-Ce^6}-1-3\implies C=\dfrac3{4e^6}[/tex]
so that the particular solution is
[tex]y=\dfrac2{1-\frac34e^{2t-6}}-1-t=\boxed{\dfrac8{4-3e^{2t-6}}-1-t}[/tex]